GUERRILA MARKETING IN 30 DAYS - Levinson, Jay Conrad, (Entrepreneur PRESS, 2014)
Updated with fresh examples, the latest techniques and trends, new success stories, and fresh, practical marketing habits for today's aspiring guerrillas, this new edition provides marketers with the latest guerrilla marketing tools and tactics. In just 30 chapters and 30 days, famous marketers Jay Conrad Levinson and Al Lautenslager show eager entrepreneurs how to zero in on their marketing goals and maximize their profits. New marketers learn from updated real-life examples and success stories and proven fundamental concepts, and use daily exercises to take their marketing to the next level -- ultimately increasing profits, cutting costs, and gaining new customers. Topics detailed in this new edition include proximity marketing, thought leadership, integration of online and offline marketing, speaking and events, direct email, personalization, and implementation. With every step, Levinson and Lautenslager provide thorough action plans to help aspiring guerrillas stay on track, leaving no excuse for anything but success.